Prescribing of FDA-approved and compounded hormone therapy differs by specialty. Issue 10 (October 2016) - Constantine, Ginger D.; Archer, David F.; Graham, Shelli; Bernick, Brian A.; Mirkin, Sebastian
Abstract : Supplemental Digital Content is available in the text Abstract: Objective: To determine the prescribing patterns of general practitioners (GPs), obstetrician/gynecologists (OB/GYNs), and wellness physicians (WPs) of menopausal hormone therapy (HT) for both compounded (CHT) and Food and Drug Administration (FDA)-approved products, using a survey of US physicians. Methods: Nine thousand one US physicians were invited to participate in a survey to report on their HT-prescribing patterns. Physicians were eligible if they prescribed HT for at least six patients per month. Results: The survey was completed by 440 eligible physicians (893 responded of 9, 001 invited) including 171 GPs, 170 OB/GYNs, and 84 WPs. Physicians prescribed HT for 15% to 30% of their female patients, with WPs numerically most likely to prescribe HT. Menopausal symptoms were the leading reason for HT prescriptions among all specialties. WPs seemed more likely to prescribe HT for general/cardiovascular health (28%), and for shorter durations, than other specialties. WPs prescribed proportionally more compounded (vs FDA-approved) estrogens/progestogens than GPs or OB/GYNs, but OB/GYNs seemed to prescribe more compounded dehydroepiandrosterone and testosterone (prescribed alone) than did others. OB/GYNs seemed least likely to consider CHT being more safe or effective than FDA-approved HT. Symptom relief was the main determinant of efficacy for all specialties; WPs also used blood (61%) or saliva testing (25%) for dose adjustment. Conclusions: Although all physician specialties surveyed prescribed HT, differences in prescribing CHT versus FDA-approved formulations by medical specialty/practice seemed to exist. Of those surveyed, OB/GYNs and GPs prescribed proportionally more FDA-approved HT, whereas WPs, similarly, prescribed more CHT. More discussion is needed concerning physicians' decisions to prescribe CHT versus FDA-approved formulations.